Penyebab Pending Klaim Berdasarkan Aspek Diagnosis dan Ketepatan Kode Diagnosis - Oktamianiza, Oktamianiza; Rahmadhani, Rahmadhani; Yulia, Yulfa; Ilahi, Vitratul; Putri, Kalasta Ayunda; Juwita, Fenty Salma (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
The pending BPJS claim occurred due to the rejection of the file by the BPJS health verifier. Problems with pending claims are caused by errors in determining the main diagnosis, incomplete diagnosis writing and code accuracy. This research aims to describe the causes of pending claims, including from the diagnostic aspect, namely the accuracy of the main diagnosis and the completeness of writing diagnosis as well as aspects of the accuracy of the diagnosis code. The research is descriptive in nature and the population is 35 medical records pending inpatient claims for 2023, the sample was determined by total sampling. The research data was analyzed univariately to determine the frequency distribution of causes of pending claims. The results of research on 35 pending claims showed that the accuracy of determining the main diagnosis was 19(54.3%), the accuracy of writing an incomplete diagnosis was 31(88.6%), and the accuracy of the incorrect diagnosis code was 29(82.9%). It is hoped that the doctor who is responsible for determining and writing the diagnosis can pay attention to the correctness of the diagnosis in the medical record and the coder can determine the correct diagnosis code based on ICD-10 and ICD-9 CM.